Does impaired processing of pro-B-type (or brain) natriuretic peptide cause decreased plasma BNP levels in obese heart failure patients? - Nishikimi, Toshio; Nakagawa, Yasuaki (Annals of Translational Medicine, 2019)
The natriuretic peptide system consists of three distinct endogenous peptides: atrial natriuretic peptide (ANP), brain (or B-type) natriuretic peptide (BNP), and C-type natriuretic peptide (CNP), as well as three receptors: natriuretic peptide receptor-A (NPR-A or guanynyl cyclase-A), natriuretic peptide receptor-B (NPR-B or guanynyl cyclase-B) and natriuretic peptide receptor-C (NPR-C or clearance receptor) (1). ANP and BNP are cardiac hormones, with ANP produced mainly in the atria and BNP produced mainly in the ventricles.